Sensory and chemical profile of a phenolic extract from olive mill waste waters in plant-base food with varied macro-composition - De Toffoli, A.; Monteleone, E.; Bucalossi, G.; Veneziani, G.; Fia, G.; Servili, M.; Zanoni, B.; Pagliarini, E.; Gallina Toschi, T.; Dinnella, C. (Food research international, 2019)
Phenols from olive mill waste water (OMWW) represent valuable functional ingredients. The negative impact on sensory quality limits their use in functional food formulations. Chemical interactions phenols/biopolymers and their consequences on bioactivity in plant-base foods have been widely investigated, but no studies to date have explored the variation of bitterness, astringency and pungency induced by OMWW phenols as a function of the food composition. The aim of the paper was to profile the sensory and chemical properties of phenols from OMWW in plant-base foods varied in their macro-composition. Four phenol concentrations were selected (0.44, 1.00, 2.25, 5.06 g/kg) to induce significant variations of bitterness, sourness, astringency and pungency in three plant-base food: proteins/neutral pH – bean purée (BP), starch/neutral pH – potato purée (PP), fiber/low pH – tomato juice (TJ). The macro-composition affected the amount of the phenols recovered from functionalized food. The highest recovery was from TJ and the lowest from BP. Two groups of 29 and 27 subjects, trained to general Labelled Magnitude Scale and target sensations, participated in the evaluation of psychophysical curves of OMWW phenols and of functionalized plant-base foods, respectively. Target sensations were affected by the food macro-composition. Bitterness increased with phenol concentration in all foods. Astringency and sourness slightly increased with concentration, reaching the weak-moderate intensity at the highest phenol concentration in PP and TJ only. Pungency was suppressed in BP and perceived at weak-moderate intensity in PP and TJ sample at the highest phenol concentration. Proteins/neutral pH plant-food (BP) resulted more appropriate to counteract the impact of added phenol on negative sensory properties thus allowing to optimize the balance between health and sensory properties. [Display omitted] •Food macro-composition affects the amount of recovered phenols.•The lowest recovery was from proteins/neutral pH plant-food.•Intensities of sensations depend by phenol concentration and food macro-composition.•Proteins/neutral pH food counteracted phenol induced “warning” sensations.